Cardiovascular protection of YiyiFuzi powder and the potential mechanisms through modulating mitochondria-endoplasmic reticulum interactions - Ding, Jingyi; Ji, Ran; Wang, Ziyi; Jia, Yuzhi; Meng, Tiantian; Song, Xinbin; Gao, Jing; He, Qingyong (Frontiers in Pharmacology, 2024)
Cardiovascular diseases (CVD) remain the leading cause of death worldwide and represent a major public health challenge. YiyiFuzi Powder (YYFZ), composed of Coicis semen and Fuzi, is a classical traditional Chinese medicine prescription from the Synopsis of Golden Chamber dating back to the Han Dynasty. Historically, YYFZ has been used to treat various CVD, rooted in Chinese therapeutic principles. Network pharmacology analysis indicated that YYFZ may exhibit direct or indirect effects on mitochondria-endoplasmic reticulum (ER) interactions. This review, focusing on the cardiovascular protective effects of Coicis semen and Fuzi, summarizes the potential mechanisms by which YYFZ acts on mitochondria and the ER. The underlying mechanisms are associated with regulating cardiovascular risk factors (such as blood lipids and glucose), impacting mitochondrial structure and function, modulating ER stress, inhibiting oxidative stress, suppressing inflammatory responses, regulating cellular apoptosis, and maintaining calcium ion balance. The involved pathways include, but were not limited to, upregulating the IGF-1/PI3K/AKT, cAMP/PKA, eNOS/NO/cGMP/SIRT1, SIRT1/PGC-1α, Klotho/SIRT1, OXPHOS/ATP, PPARα/PGC-1α/SIRT3, AMPK/JNK, PTEN/PI3K/AKT, β2-AR/PI3K/AKT, and modified Q cycle signaling pathways. Meanwhile, the MCU, NF-κB, and JAK/STAT signaling pathways were downregulated. The PERK/eIF2α/ATF4/CHOP, PERK/SREBP-1c/FAS, IRE1, PINK1-dependent mitophagy, and AMPK/mTOR signaling pathways were bidirectionally regulated. High-quality experimental studies are needed to further elucidate the underlying mechanisms of YYFZ in CVD treatment.